A fibrinogen-related protein identified from hepatopancreas of crayfish is a potential pattern recognition receptor. (September 2016) - Chen, Qiming; Bai, Suhua; Dong, Chaohua
Abstract: Fibrinogen-related protein (FREP) family is a large group of proteins containing fibrinogen-like (FBG) domain and plays multiple physiological roles in animals. However, their immune functions in crayfish are not fully explored. In the present study, a novel fibrinogen-like protein (designated as PcFBN1) was identified and characterized from hepatopancreas of red swamp crayfish Procambarus clarkii . The cDNA sequence of PcFBN1 contains an open reading frame (ORF) of 1353 bp encoding a protein of 450 amino acids. Sequence and structural analysis indicated that PcFBN1 contains an FBG domain in C-terminal and a putative signal peptide of 19 amino acids in N -terminal. Semi-quantitative PCR revealed that the main expression of PcFBN1 was observed in hepatopancreas and hemocyte. Temporal expression analysis exhibited that PcFBN1 expression could be significantly induced by heat-killed Aeromonas hydrophila . Tissue distribution and temporal change of PcFBN1 suggested that PcFBN1 may be involved in immune responses of red swamp crayfish. Recombinant PcFBN1 protein binds and agglutinates both gram-negative bacteria Escherichia coli and gram-positive bacteria Micrococcus lysodeikticus . Moreover, binding and agglutination is Ca 2+ dependent. Further analysis indicated that PcFBN1 recognizes some acetyl group-containing substance LPS and PGN. RNAi experiment revealed that PcFBN1 is required for bacterial clearance and survival from A. hydrophila infection. Reduction of PcFBN1 expression significantly decreased the survival and enhanced the number of A. hydrophila in the hemolymph. These results indicated that PcFBN1 plays an important role in the innate immunity of red swamp crayfish as a potential pattern recognition receptor. Highlights: A novel FREP was identified from heptopancreas of crayfish. Expression analysis suggested that PcFBN1 is involved in immune responses of crayfish. PcFBN1exhibited strong Bacteria-binding property and ligand-binding specificity. RNAi-mediated silencing indicated that the protein is required for bacterial clearance and survival.